Dephosphorylation of endotoxin by alkaline phosphatase in vivo. - Poelstra, K. (1997)
Natural substrates for alkaline phosphatase (AP) are at present not identified despite extensive investigations. Difficulties in imagining a possible physiological function involve its extremely high pH optimum for the usual exogenous substrates and its localization as an ecto-enzyme. As endotoxin is a substance that contains phosphate groups and is usually present in the extracellular space, we studied whether AP is able to dephosphorylate this bacterial product at physiological pH levels. We tested this in intestinal cryostat sections using histochemical methods with endotoxin from Escherichia coli and Salmonella minnesota R595 as substrate. Results show that dephosphorylation of both preparations occurs at pH 7.5 by AP activity. As phosphate residues in the lipid A moiety determine the toxicity of the molecule, we examined the effect of the AP inhibitor levamisole in vivo using a septicemia model in the rat. The results show that inhibition of endogenous AP by levamisole significantly reduces survival of rats intraperitoneally injected with E. coli bacteria, whereas this drug does not influence survival of rats receiving a sublethal dose of the gram-positive bacteria Staphylococcus aureus. In view of the endotoxin-dephosphorylating properties of AP demonstrated in vitro, we propose a crucial role for this enzyme in host defense. The effects of levamisole during gram-negative bacterial infections and the localization of AP as an ecto-enzyme in most organs as well as the induction of enzyme activity during inflammatory reactions and cholestasis is in accordance with such a protective role.